Saints Gone Monastic: The Dominican Cult of Saints in the Medieval Baltic Sea Region - Gøgsig Jakobsen, Johnny Grandjean (Journal of Medieval Monastic Studies, 2019)
Abstract Unlike several other monastic orders of the Middle Ages, the mendicant orders of Dominicans and Franciscans chose from an assorted list of saints as patrons and patronesses for their friary churches and for their many side altars which were also dedicated to a broad variety of saints. These were not just venerated by the friars internally, but also used in their pastoral connection to the lay public as central figures in sermons, processions, and intercessory prayers. This article identifies a ‘short list’ of particularly popular saints among the Dominicans in the Baltic Sea region, with a comparative look at the local Franciscans as well as the neighbouring Dominican provinces. For both orders an outspoken preference for female saints (the Holy Virgin, Mary Magdalene, St Catherine of Alexandria, and, later, St Anne) can be noted in the region, while devotion to male saints (especially St John, St Nicholas, and St Olav) appears with significant sub-regional variations. Although some veneration of St Dominic and St Peter Martyr can be noted, the Dominican Order never seems to have attempted any major promotion of their own saints in the Baltic Sea region.